Kesejahteraan Psikologis Gig Worker: Studi Fenomenologis pada Pekerja Pengemudi Ojek Online dan Freelancer - Anisah Zaqiyatuddinni (Universitas Paramadina, 2026)
The growing number of workers engaged in flexible yet unstable employment systems underscores the importance of examining the psychological well-being of gig workers. In this study, psychological well-being is conceptualized as an individuals capacity for self acceptance, positive relationships, autonomy, environmental mastery, purpose in life and personal growth. Gig workers are defined as individuals engaged in flexible, project based, or on demand work arrangements without formal employment contracts or stable job security. This study aims to explore the lived experiences of psychological well-being among online motorcycle taxi drivers and freelancers. A qualitative method with a phenomenological approach was employed. Participants were selected purposively, comprising six individuals namely three online motorcycle taxi drivers and three freelancers in graphic design, tutoring, and human resource recruitment. Data were collected through in depth interviews and analyzed using thematic analysis, without involving additional informants beyond the primary participants. The findings reveal that psychological well-being among gig workers is shaped through adaptive processes in response to unstable working conditions. Participants demonstrated self acceptance, supportive social relationships and autonomy in managing their time and work related decisions. They also exhibited environmental mastery through adaptive strategies, derived meaning in life from both family responsibilities and self actualization and experienced personal growth through ongoing work related challenges. These findings suggest that psychological well-being is not solely determined by income stability but is also influenced by the ability to construct meaning, maintain social connectedness and develop flexibility in navigating work uncertainty.